2021
DOI: 10.1200/op.20.00892
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of the Involvement of Dentists in Managing Oral Complications Among Patients With Oral Cavity and Oropharyngeal Cancer: An Analysis of Claims Data

Abstract: PURPOSE: Patients with oral cancer and oropharyngeal cancer frequently develop treatment-related oral complications that negatively affect patients' quality-of-life, cost, and health outcomes. We investigated whether the provider specialty affected the costs and treatment duration of managing oral complications. METHODS: Using deidentified claims from a commercial insurer from 2008 to 2019, we compared costs and duration of common oral complication management between patients whose care included a dentist, wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 29 publications
0
9
0
1
Order By: Relevance
“…Although the cost was higher when management of chronic complication involved a dentist, the average treatment duration was shorter than that of their counterparts. (21) Patients who are under active cancer therapy, and those with a history of cancer treatment may face difficulty obtaining proper dental care since general dentists often lack the necessary experience needed to effectively manage these patients. (22) Hence, early integration of specialized dental providers to the care teams of cancer patients holds a significant long-term benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Although the cost was higher when management of chronic complication involved a dentist, the average treatment duration was shorter than that of their counterparts. (21) Patients who are under active cancer therapy, and those with a history of cancer treatment may face difficulty obtaining proper dental care since general dentists often lack the necessary experience needed to effectively manage these patients. (22) Hence, early integration of specialized dental providers to the care teams of cancer patients holds a significant long-term benefit.…”
Section: Discussionmentioning
confidence: 99%
“…Oral and dental complications of cancer treatment have been previously shown to negatively affect patient health and lead to higher costs of care. 24 A total of 39% of patients who reported seeing a dentist more than twice a year after cancer treatment reported financial difficulty compared with 18% of those who went to a dentist twice yearly before cancer treatment. A previous study found that involving dentists in the care of patients with HNC was associated with decreased costs and shorter treatment times, emphasizing the role of dentists in HNC care teams.…”
Section: Discussionmentioning
confidence: 99%
“…6,7,8 O controle do quadro de MO também é de interesse dos planos e seguros de saúde visto que quanto menor for a gravidade da MO, menor serão os gastos dos planos e seguros com o beneficiário em questão, evitando necessidade de internação hospitalar, alimentação via sonda nasoenteral e interrupção do tratamento, o que irá interferir diretamente na sobrevida e qualidade de vida do paciente. 24,25,26 Torna-se essencial a divulgação em grande escala aos colegas cirurgiões dentistas sobre como intervir junto ao plano/seguro de saúde para favorecer o paciente, gerando menos complicações, sofrimento adicional e custos para todas as partes envolvidas, além de proporcionar alívio ao sofrimento durante o período do tratamento do câncer e melhorar a qualidade de vida.…”
Section: A Saúde Suplementarunclassified